2016
DOI: 10.1080/09537325.2016.1180352
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the influence of differentiation strategy and R&D subsidies on R&D cooperation

Abstract: This paper explores the R&D cooperation determinants of the innovative companies belonging to the Spanish manufacturing sector. Our findings suggest that the variable R&D subsidy is endogenous, significant, and has a strong positive influence on R&D cooperation. This is a clear indication that the achievement of public aid is often conditioned by the obligation for companies to cooperate in R&D. We have also found that the differentiation strategy variable is significant and has a negative influence on R&D coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Duguet used data from French companies and confirmed that government support does not crowd out corporate R&D investment (Duguet, 2003). Gonzfilez et al studied the relationship between government R&D grants and corporate R&D investment in 2005 and 2008, respectively and confirmed the effect of government R&D grants on corporate R&D spending was positive and significant (Guisadogonzález, Ferrosoto, & Guisadotato, 2016). Mu Tian studied the effect of public R&D spending on R&D expenditures using a linear regression model.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Duguet used data from French companies and confirmed that government support does not crowd out corporate R&D investment (Duguet, 2003). Gonzfilez et al studied the relationship between government R&D grants and corporate R&D investment in 2005 and 2008, respectively and confirmed the effect of government R&D grants on corporate R&D spending was positive and significant (Guisadogonzález, Ferrosoto, & Guisadotato, 2016). Mu Tian studied the effect of public R&D spending on R&D expenditures using a linear regression model.…”
Section: Introductionmentioning
confidence: 97%
“…Guisado‐Gonzalez considered R&D subsidies endogenous and have a significant positive effect on research and development cooperation. The company that released the differentiation strategy needs more public policy to support R&D (Guisado‐Gonzalez, Ferro‐Soto, & Guisado‐Tato, ). Miranda Victorio built a model of government‐subsidized project selection based on literature and analytic hierarchy process and verified the applicability of the model (Victório, Costa, & Souza, ).…”
Section: Introductionmentioning
confidence: 99%
“…Its major role in innovation processes stems from the fact that cooperation creates opportunities to gain complementary resources and skills, and as a consequence, can lead to faster development of innovations [Kubera, 2021]. The innovation collaborative network can be established not only with universities or research institutes, but also with industrial actors, including suppliers, users, complementors and even rivals as well [Guisado-González et al, 2016]. Network additionality can be viewed as a firm-level one-off effect, when a beneficiary firm enters into collaboration only to carry out the subsidized project, or a firm-level persistent effect (e.g., due to a public intervention, a firm changes the pattern in which it cooperates with others); or system-level effect, in the form of, for example, improved coordination [Kubera, 2021].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In country-level spillovers, the typical effect is that the host country receives new knowledge on technology and management indirectly through the local subsidiaries of MNCs (Blomström and Kokko 1998;Glass and Saggi 2002;Nursamsu and Hastiadi 2015;Yi et al 2015;Yunus et al 2015;Zhang et al 2010;Zhao 2021). Prior studies on spillovers at the industry level have been concerned with the effect of firms indirectly obtaining technological knowledge from the R&D activities of competitors in the same industry (Aldieri and Vinci 2017;Audretsch and Belitski 2020;Guisado-González et al 2016;Hájek and Stejskal 2018;Lamin and Ramos 2016;Ramadani et al 2017;Ryu et al 2018;Venturini et al 2019). As for firm-level spillovers, research has been carried out on the effects of headquarters receiving foreign knowledge from returning managers (Tzeng 2018).…”
Section: Learning By Teachingmentioning
confidence: 99%